SOFIA/FIFI-LS Full-disk [C ii] Mapping and CO-dark molecular gas across the nearby spiral galaxy NGC 6946 - Bigiel, Frank; Cormier, Diane (The astrophysical journal, 2020)
We present SOFIA/FIFI-LS observations of the [C ii] 158 μm cooling line across the nearby spiral galaxy NGC 6946. We combine these with UV, IR, CO, and H i data to compare [C ii] emission to dust properties, star formation rate (SFR), H2, and H i at 560 pc scales via stacking by environment (spiral arms, interarm, and center), radial profiles, and individual, beam-sized measurements. We attribute 73% of the [C ii] luminosity to arms, and 19% and 8% to the center and interarm region, respectively. [C ii]/TIR, [C ii]/CO, and [C ii]/PAH radial profiles are largely constant, but rise at large radii (≳ 8 kpc) and drop in the center (“[C ii] deficit”). This increase at large radii and the observed decline with the 70 μm/100 μm dust color are likely driven by radiation field hardness. We find a near proportional [C ii]-SFR scaling relation for beam-sized regions, though the exact scaling depends on methodology. [C ii] also becomes increasingly luminous relative to CO at low SFR (interarm or large radii), likely indicating more efficient photodissociation of CO and emphasizing the importance of [C ii] as an H2 and SFR tracer in such regimes. Finally, based on the observed [C ii] and CO radial profiles and different models, we find α CO to increase with radius, in line with the observed metallicity gradient. The low α CO (galaxy average ≲ 2 M ⊙ pc−2 (K km s−1)−1) and low [C ii]/CO ratios (∼400 on average) imply little CO-dark gas across NGC 6946, in contrast to estimates in the Milky Way.
Gesehen am 03.12.2020